Effect of surface conditions of one-side patterned electrodes applied to electrorheological gel. (January 2018) - Koyanagi, Ken'ichi; Miyama, Keita; Kakinuma, Yasuhiro; Anzai, Hidenobu; Sakurai, Koji; Motoyoshi, Tatsuo; Masuta, Hiroyuki; Oshima, Toru
The use of a patterned electrode on one side only is expected to be a suitable solution for omitting the wiring to the movable electrode using electrorheological gel. Electrorheological gel is a functional material that changes the force absorbance and frictional force characteristics of its surface in response to the magnitude of an applied electric field. One problem in both the design and the application of electrorheological gels is the wiring of the electrodes that must sandwich the electrorheological gel. Thus, a one-side patterned electrode can be a desirable solution. We investigated the shear stress produced by electrorheological gel applied to such a patterned electrode during rotational and translational motion. Variation of the material of the opposing part reveals that the mechanical and electric characteristics of the electrode meaningfully affect the experienced shear stress.